The efficacy of new drug regimens in treating newly diagnosed high-risk cytogenetic multiple myeloma patients: a systematic literature review and meta-analysis - Zhou, Huixing; Chen, Wenming (Frontiers in Medicine, 2025)
IntroductionMultiple myeloma (MM) is a plasma cell malignancy comprising 10% of hematologic cancers, associated with bone marrow dysfunction and organ damage. High-risk cytogenetic MM patients, identified by specific genetic abnormalities, face poor outcomes despite recent advancements. Traditional treatments often prove inadequate, necessitating novel regimens. This review assesses the efficacy of emerging therapies—next-generation proteasome inhibitors, immunomodulatory drugs, and CD38-targeting agents—aimed at improving outcomes for this patient subset.MethodsA systematic review and meta-analysis were performed, analyzing data from 18 randomized controlled trials (RCTs) involving high-risk MM patients treated with new drug combinations. Data extraction, quality assessment, and meta-analysis were conducted using a Bayesian fixed-effects model.ResultsFor transplant-eligible patients, CD38-based therapies reduced progression or death risk by 33% during induction and 48% during maintenance. They improved progression-free survival (PFS) by 38% in induction and 57% in maintenance and increased minimal residual disease (MRD) negativity by 38%. Dual novel drug regimens also enhanced MRD negativity, but Elotuzumab and Ixazomib regimens showed limited impact. Carfilzomib-based therapies showed varying PFS and survival benefits.ConclusionCD38-targeted regimens notably improve outcomes in high-risk cytogenetic MM, especially for transplant-eligible patients, by reducing disease progression, enhancing PFS, and increasing MRD negativity. Dual novel regimens show promise in MRD improvements. These findings support the potential of tailored therapeutic strategies to optimize patient care.